RNA-Seq Highlights Molecular Events Associated With Impaired Pollen-Pistil Interactions Following Short-Term Heat Stress in Brassica napus - Lohani, Neeta; Singh, Mohan B.; Bhalla, Prem L. (Frontiers in Plant Science, 2021)
The global climate change is leading to increased frequency of heatwaves with crops getting exposed to extreme temperature events. Such temperature spikes during the reproductive stage of plant development can harm crop fertility and productivity. Here we report the response of short-term heat stress events on the pollen and pistil tissues in a commercially grown cultivar of Brassica napus. Our data reveals that short-term temperature spikes not only affect pollen fitness but also impair the ability of the pistil to support pollen germination and pollen tube growth and that the heat stress sensitivity of pistil can have severe consequences for seed set and yield. Comparative transcriptome profiling of non-stressed and heat-stressed (40°C for 30 min) pollen and pistil (stigma + style) highlighted the underlying cellular mechanisms involved in heat stress response in these reproductive tissues. In pollen, cell wall organization and cellular transport-related genes possibly regulate pollen fitness under heat stress while the heat stress-induced repression of transcription factor encoding transcripts is a feature of the pistil response. Overall, high temperature altered the expression of genes involved in protein processing, regulation of transcription, pollen-pistil interactions, and misregulation of cellular organization, transport, and metabolism. Our results show that short episodes of high-temperature exposure in B. napus modulate key regulatory pathways disrupted reproductive processes, ultimately translating to yield loss. Further investigations on the genes and networks identified in the present study pave a way toward genetic improvement of the thermotolerance and reproductive performance of B. napus varieties.